Effects of combined uphill-downhill sprinting versus resisted sprinting methods on sprint performance: a systematic review and meta-analysis - Hamad, M. J.; Alcaraz, P. E.; de Villarreal, E. S. (Sports Medicine, 2024)
Background: Two specific sprint training methods that are present to varying degrees in research and practice are combined uphill-downhill sprinting (UDS) and resisted sprint training methods (RS). Both methods seem to improve sprint performance, but to the author`s knowledge a comparison does not exist investigating the differences between the two training protocols and traditional sprinting. Objective: The present systematic review and meta-analysis investigated sprint performance changes between combined uphill-downhill sprinting and resisted sprinting methods (sleds, cables/bands, vests, uphill) and how these compared with traditional sprinting. Methods: A literature search was performed on 19 December 2022, in the databases PubMed, SPORTDiscus, Web of Science and SCOPUS, which from 22 studies yielded a total of 24 eligible groups (UDS, n = 6; RS, n = 18). Studies that measured sprint performance, had a traditional sprinting control, and used either training intervention in healthy individuals of any age for = 4 weeks were eligible for the meta-analysis. The change in sprint performance from baseline to post intervention was compared between the interventions and their traditional sprinting control group. Outcomes were expressed as standardized mean differences (SMD). Results: The standardized changes in sprint performance between intervention groups and traditional-sprinting controls (negative in favour of intervention, positive in favour of traditional sprint) and 95% confidence interval (CI) were as follows: small for UDS (SMD - 0.41 [- 0.79, - 0.03]; p = 0.03), trivial for RS (SMD - 0.14 [- 0.36, 0.07]; p = 0.19). Conclusion: Combined uphill-downhill sprinting was more effective than traditional sprinting, while resisted sprinting was not. It appears that resisted sprint interventions do not increase sprint performance any more than traditional sprinting. Subgroup analysis and meta-regression appear to show differences between sled loads and possible differences across distances tested. The results of this review and meta-analysis seem to warrant further investigations into the possibility that UDS may be a superior sprint training method to resisted and traditional sprinting.